Comparative Study based on the Effectiveness of Online & Offline Learning Outcomes - Dr. Venugopal Narsingoju, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In March 2020, Covid-19 is declared as the Global Pandemic and affected all lives, processes, systems adversely. The biggest question and challenge for Indian Education System was to switch from Traditional teaching learning pedagogy to Online Mode of Teaching. Technology has mostly changed everything but sometimes drastic changes may not give good results. This research paper has presented the comparative study based on the Effectiveness of Online and Offline Learning Outcomes. Survey is conducted to understand various aspects of Online and Offline Teaching Learning pedagogy. Students reported their problems and learning outcomes which can be easily demonstrated. The comparative study will be helpful for the operational, qualitative and quantitative Learning outcomes and will also ensure for the effective Learning outcomes.